2014
DOI: 10.1002/mnfr.201300723
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism at the TNF‐alpha gene interacts with Mediterranean diet to influence triglyceride metabolism and inflammation status in metabolic syndrome patients: From the CORDIOPREV clinical trial

Abstract: These results suggest that the rs1800629 at the tumor necrosis factor alpha gene interacts with MedDiet to influence TG metabolism and inflammation status in MetS subjects. Understanding the role of gene-diet interactions may be the best strategy for personalized treatment of MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 49 publications
4
20
0
Order By: Relevance
“…Gomez-Delgado et al reported that decreases in plasma triglyceride due to adopting a Mediterranean diet were significantly greater in 203 GG homozygotes of the tumor necrosis factor alpha gene (TNFA, rs1800629) than in 48 carriers of the A-allele, i.e. approximately 0.31 vs. 0.12 mmol/L, respectively (P = 0.005) 64 . However, plasma triglyceride concentrations averaged approximately 1.80 mmol/L at baseline and 1.52 mmol/L on the diet, and correspondingly, the differences between the GG and GA/AA genotypes were 0.38 vs. 0.19 mmol/L, respectively.…”
Section: Smokingmentioning
confidence: 99%
“…Gomez-Delgado et al reported that decreases in plasma triglyceride due to adopting a Mediterranean diet were significantly greater in 203 GG homozygotes of the tumor necrosis factor alpha gene (TNFA, rs1800629) than in 48 carriers of the A-allele, i.e. approximately 0.31 vs. 0.12 mmol/L, respectively (P = 0.005) 64 . However, plasma triglyceride concentrations averaged approximately 1.80 mmol/L at baseline and 1.52 mmol/L on the diet, and correspondingly, the differences between the GG and GA/AA genotypes were 0.38 vs. 0.19 mmol/L, respectively.…”
Section: Smokingmentioning
confidence: 99%
“…15 In this research, we genotyped three APOE SNPs (rs439401, rs440446 and rs7412) previously reported in the literature linked with lipid metabolism and CVD. 15 In this research, we genotyped three APOE SNPs (rs439401, rs440446 and rs7412) previously reported in the literature linked with lipid metabolism and CVD.…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Biochemical measurements, deoxyribonucleic acid (DNA) isolation and genotyping have been previously described. 15 In this research, we genotyped three APOE SNPs (rs439401, rs440446 and rs7412) previously reported in the literature linked with lipid metabolism and CVD. 16,17…”
Section: Laboratory Testsmentioning
confidence: 99%
“…There are very few dietary intervention trials with MedDiet analyzing gene-diet interactions on cardiovascular phenotypes. We have summarized the current evidence of reported interactions in Table 3 [ 63 , 64 , 75 , 76 , 77 , 78 ]. Moreover, only the PREDIMED study has analyzed gene-diet interactions from intervention with MedDiet in determining hard cardiovascular end points (total CVD incidence, stroke, myocardial infarction, CVD mortality, etc.).…”
Section: Omic Biomarkers In the Predimed Study And In Other Studiementioning
confidence: 99%